Fine alpha in current and newly developed Ti alloys. (July 2019) - Wang, M.; Lu, Y.; Pang, B.; Kloenne, Z.T.; Fraser, H.L.; Chiu, Y.L.; Loretto, M.H.
Abstract: Analytical transmission electron microscopy has been used to determine the chemical compositions of beta grains in samples of HIPped powder Ti6Al4V, cooled in the HIP at approximately 5 °C/min in order to understand their different microstructures. It has been found that beta grains, which contain a high density of fine secondary alpha phase, have compositions (wt%) of about 81%Ti; 3%Al; 14%V and 2%Fe. This analysis includes both the fine secondary alpha and the beta in the grain and thus corresponds to the composition of the parent beta grain. Grains of retained beta, which do not contain any fine secondary alpha, are stabilised by a much higher V-content and contain about 75%Ti; 3%Al, 20%V and 2%Fe. The diffraction patterns from the grains that contain secondary alpha show maxima from several habits of alpha as well as beta maxima, whereas the beta grains, which contain no secondary alpha, show only beta maxima together with diffuse scattering. These observations provide the data needed to understand the factors that lead to the different microstructures observed in beta grains in slowly cooled HIPped powder Ti64 and suggest that an alloy, of a composition close to that of the beta grains in Ti64, which contain fine secondary alpha, should also contain a large fraction of fine alpha, when slowly cooled. This has been confirmed and the microhardness of slowly cooled samples has been shown to be higher than that of air-cooled Ti64. Graphical abstract: Microstructure of new alloy (a) Slowly cooled sample (b) Held for 2 h at 600 °C after slow cooling.Image 1